Intravenous thrombolytic for 16 patients with stroke warning syndrome - Jing⁃yu PENG (Chinese Journal of Contemporary Neurology and Neurosurgery, 2020)
Objective To evaluate the clinical characteristics, imaging manifestations and the efficacy and safety of intravenous thrombolytic for patients with stroke warning syndrome (SWS). Methods Sixteen patients with SWS from January 2017 to July 2019 were reviewed. The rt ⁃ PA intravenous thrombolysis and antiplatelet, lipid adjusting were treated. National Institutes of Health Stroke Scale (NIHSS) was performed to evaluate neurological function and modified Rankin Scale (mRS) was performed to evaluate prognosis, and to observe the presence of hemorrhagic transformation (HT) and recurrence of stroke. Results The most frequent preexisting risk factors were hypertension (13 cases), hyperhomocysteinemia (12 cases), dyslipidemia (9 cases) and smoking history (10 cases). All patients presented with pure motor syndrome (n = 7) or sensory motor syndrome (n = 9). All patients had 3-9 clinical fluctuations before treatment and the duration of symptoms ranged from 3-240 min. In 13 of 16 SWS patients, DWI showed acute cerebral infarctions. CTA or MRA showed atherosclerotic plaques in 14 cases. Thirteen patients experienced favorable recovery, complete remission (5/16), significant remission (1/16) and partial remission (7/16), respectively. Fourteen patients reached favorable outcome (mRS < 2 at 3 months). NIHSS score at 24 h after intravenous thrombolytic and at discharge were lower than that on admission and the maximum value in the course of disease (P = 0.000, for all), while NIHSS score on admission and the maximum value in the course of disease (P = 0.433), and at 24 h after intravenous thrombolytic and discarge time (P = 0.054), were no significant statistical difference. Conclusions Intravenous thrombolysis may be a potentially effective therapy for patients with SWS within the therapeutic time window. DOI：10.3969/j.issn.1672⁃6731.2020.05.011